1996
DOI: 10.1210/mend.10.12.8961276
|View full text |Cite
|
Sign up to set email alerts
|

The carboxy-terminal region of the beta-subunits of luteinizing hormone and chorionic gonadotropin differentially influence secretion and assembly of the heterodimers.

Abstract: One of the major structural differences between the LH beta and CG beta subunits is the carboxy-terminal region: beyond amino acid 114, LH beta has a hydrophobic heptapeptide stretch, while CG beta contains a 31-amino acid hydrophilic carboxy-terminal peptide (CTP) that is O-glycosylated. The CG beta subunit is secreted quantitatively as a monomer and assembles efficiently whereas secretion and assembly of LH beta is inefficient. We previously implicated the carboxy-terminal heptapeptide as a determinant for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
(3 reference statements)
3
18
0
Order By: Relevance
“…The hydrophilic CTP of hCG contains determinants that favor the secretion of recombinant hLH and hFSH when fused to the C-terminus of their b-subunits (Fares et al 1992, Muyan et al 1996. We also showed that deletion of the CTP downstream of residue 111 in the dimeric eLH/CG (aebe111LH/CG) induces a 50% decrease in the secretion of the truncated hormone compared with the full-length aebeLH/CG (Galet et al 2000) as detected by ELISA.…”
Section: Introductionmentioning
confidence: 59%
“…The hydrophilic CTP of hCG contains determinants that favor the secretion of recombinant hLH and hFSH when fused to the C-terminus of their b-subunits (Fares et al 1992, Muyan et al 1996. We also showed that deletion of the CTP downstream of residue 111 in the dimeric eLH/CG (aebe111LH/CG) induces a 50% decrease in the secretion of the truncated hormone compared with the full-length aebeLH/CG (Galet et al 2000) as detected by ELISA.…”
Section: Introductionmentioning
confidence: 59%
“…Fusing the hCG␤-CTP to the bovine LH␤ subunit resulted in a hormone with a longer halflife and various abnormalities related to the LH excess when this LH␤-CTP chimera was expressed in a transgenic mouse model (15). Although the hydrophobic carboxyl-terminal end of the hLH␤ subunit is involved in the intracellular retention of the protein, the hydrophilic CTP stretch of hCG␤ contains determinants that are favorable for secretion and, when fused to the ␤-subunits of human LH and human follitropin, enhance the release from transfected cells (14,16,17). In vivo, the storage and secretion profiles of the hormones differ; hLH is stored in secretagogue-sensitive granules, and there are data showing it is secreted from the basolateral surface of the pituitary gonadotropes (18 -20).…”
mentioning
confidence: 99%
“…Moreover, the different ELISAs used an anti-mAb and this subunit was never mutated, so we could reasonably assume that its epitope is always intact. It is now well established that the CTP and the 26-110 disulphide bridge of the hCG subunit are involved in the intracellular trafficking and secretion of the hCG heterodimer (Suganuma et al 1989, Huth et al 1993, Muyan et al 1996. It seems to be the same for eLH/CG, particularly for the 26-110 disulphide bridge since its deletion induced a severe decrease in the heterodimer production but no decrease in the single chain production (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…The CTP of the hCG subunit has been shown to be involved in the half-life of the hormone (Matzuk et al 1990). It is not implicated in in vitro biological activity but is required for the correct intracellular folding of the dimer (Matzuk et al 1989, Muyan et al 1996, Muyan & Boime 1998.…”
Section: Introductionmentioning
confidence: 99%